The Antarctic fish Harpagifer antarcticus under current temperatures and salinities and future scenarios of climate change. (May 2019) - Navarro, Jorge M.; Paschke, Kurt; Ortiz, Alejandro; Vargas-Chacoff, Luis; Pardo, Luis Miguel; Valdivia, Nelson
Highlights: H. antarcticus is able to cope with a moderate temperature increase in the Antarctic. A drastic increment in mortality was observed with seawater warming. The stenothermal nature of H. antarcticus was confirmed. Abstract: Antarctic coasts are highly vulnerable environments where temperature have remained very constant along millions of years. These unique environmental conditions have generated a large number of stenoic species that could be highly sensitive to future scenarios of climate change. We investigated the separate and interactive effects of increasing seawater temperature and decreasing salinity on the physiological performance of the notothenioid fish, Harpagifer antarcticus . Adult individuals were exposed to an orthogonal combination of five temperatures (2, 5, 8, 11, 14 °C) and three salinities (23, 28, 33 psu) for a 10-day period. A drastic increment in mortality was observed with seawater warming; the pattern in response to lower salinity was less clear. No fish died at the two lowest temperatures (2 and 5 °C); however, mortality increased significantly at the two highest temperatures across the salinity treatments (33.3% at 11 °C; 93.3% at 14 °C). No data were obtained at 14 °C that could be included in the physiological analyses. Ingestion and absorption rates were significantly affected by temperature and salinity, but not by the interaction of the two. Finally, we observed a negative effect of temperature but not of salinity or the interaction of both on the scope for growth of H. antarcticus . These results suggest that this species could cope with a moderate temperature increase (5 °C) in the Antarctic. However, the higher metabolic rates observed at 8 and 11 °C are associated with conditions beyond the natural thermal window of this species, representing a disadvantage in the face of climate change. Therefore, and even in the hypothetical case that H. antarcticus were able to disperse to sub-Antarctic areas such as the Magellan Region, current and projected scenarios of seawater temperatures might be unsuitable for the development of effective populations of this species. The results confirm the stenothermal nature of H. antarcticus, considering its high vulnerability to environmental changes and its limited ability to cope with the more severe global warming models projected for the Antarctic and Magellan regions for the end of the century (mainly temperature).